Adaptive-Fuzzy back stepping control of cable robot vessels - Mohammadreza Barzegaran; Sana Tajvidi; Majid Alimohammadi (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
Importance of sea in development, promotion and safety of the related countries make access to data and recognizing the environment become very important. Surface vessels help access to sea easier regarding technological advancement. Controlling surface vessels is considered as an active field of research regarding offshore, military and research uses. The main problem of controlling surface vessels is that these vehicles are often underactuated. Underatuation means that the system has lower number of independent actuators than degrees of freedom. In this study, designing an output feedback controller in the presence of parametric and non-parametric uncertainties independent of speed signal measurement and regarding actuators dynamic for path tracking of underactuated surface vessels, was studied. In designing controller, dynamic surface control method is used in order to reduce complexity of back stepping control.